Learning energy storage in hybrid/electric vehicles: Erasmus Mundus Master Course in Sustainable Transportation & Electrical Power Systems - Diaz, J.; Pernia, A.M.; Guerrero, J.M.; Pereirinha, Paulo G.; Williams, Arthur (2016)
The "Erasmus Mundus Master Course in Sustainable Transportation & Electrical Power Systems" is supported by three universities, located in Spain, Italy and United Kingdom, and a Polytechnic Institute in Portugal. One of the main goals is the training of qualified staff in areas related to electrical energy management, emphasizing in power systems for electric propulsion vehicles and renewable energies. Among others, the subject "Energy Storage and Recovery in Power Systems and Hybrid/Electric Vehicles" is considered a keystone in the Master. During third semester, the students who follow the technical track, have to develop small projects and tasks related to electric vehicles, battery management, power stages for battery charger and so on. This paper show the goals and the results obtained in these topics. All of these topics are partially collected in one subject, with a high practical content. The students have to learn not only the theoretical topics, but they have to elaborate a project, in a work team and use modern laboratory equipment as well. It should be noted that the students have to work and collaborate in a multicultural environment, with students and professors. This paper describes the subject methodology, and the results obtained.